Aortic Blunt Trauma Analysis during a Frontal Impact - Mario Alberto Grave-Capistrán; Arturo Yishai Prieto-Vázquez; Christopher René Torres-SanMiguel (Applied Bionics and Biomechanics)
The aorta is the largest artery of the human body, and it is considered in the continuous medium mechanics as a hyperelastic material for its biological properties. The thoracic aorta is directly affected in vehicular collision events by compression generated between the ribcage and the three-point seatbelt tension producing injuries in the artery wall. A three-dimensional model of the thoracic aorta was constructed from digital tomographic images considering the ascending aorta, the aortic arch, and the descending aorta. The model obtained presents acceptable characteristics such as a length of 222.8 mm and an ascending aortic diameter of 22.7 mm, 22.7 mm in the aortic arch, and 16.09 mm in the descending aorta. A 150 ms time numerical simulation was developed through the finite element method (MEF), and the model was analyzed simulating a compression load on the artery at its front location. Boundary conditions were considered by selecting specific nodes in the model, such as the points where the artery is held in the thorax with other elements. In addition, displacement nodes were considered to establish a natural behavior of the artery. The outcomes show significant displacements in the artery wall. The most affected areas are the aortic arch and descending aorta, whose displacements reach 14 mm from their original position. Based on the abbreviated injury scale (AIS), the degree of injury to the aorta in this collision event is estimated, an AIS 2 with a moderate severity index and required medical attention.